Prevalence and Severity of Breast Arterial Calcification on Routine Mammography - E. V. Bochkareva; E. K. Butina; E. Kh. Bayramkulova; O. V. Molchanova; N. I. Rozhkova; N. E. Gavrilova; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
Aim. To determine the frequency of detection and severity of breast arterial calcification (BAC) among women undergoing mammography on the basis of medical institutions in Moscow.Material and methods. The analysis included 4274 digital mammograms of women aged 40-93 who underwent preventive or diagnostic mammography. Standard full-format digital mammograms were performed in craniocaudal and mediolateral oblique projections. In addition to the standard diagnosis of breast disease, all mammograms were evaluated for the presence of BAC. The severity of BAC was assessed on a 12-point scale: mild 3-4 points, moderate 5-6 points, severe 7-12 points.Results. The average frequency of BAC was 10.1%, in the middle age group 50-59 years – 6.0%. The incidence of BAC increased with age, from 0.4% to 0.6% in women <50 years of age to >50% in women ≥80 years of age. A statistically significant and pronounced correlation was found between the woman's age and the presence of BAC r Pearson =0.769 (p<0.001). There was also a less noticeable but statistically significant correlation between age and severity of BAC r Spearman =0.319 (p<0.001). Regression analysis made it possible to estimate the probability of CAD depending on age. In women <50 years of age, only mild to moderate calcification occurred, while those ≥65 years of age had a significant increase in the incidence of severe CAD.Conclusion. There was an expected increase with age in both prevalence and severity of BAC. Cases of severe BAC in women younger than 65 years of age and any BAC in women younger than 50 years of age are atypical and require clarification of their association with cardiovascular and other diseases.